ACCOUNTING LEARNING MAPPING BASED ON INDIVIDUAL CHARACTERISTIC UNIVERSITY STUDENTS IN MEDAN CITY - Henny Zurika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to reveal the interest of students studying accounting based on individual characteristics.The population of this research is students at private university in medan city,especially on faculcity of economics of accounting study program.